2011
DOI: 10.1371/journal.pone.0027379
|View full text |Cite
|
Sign up to set email alerts
|

Does Tinnitus Distress Depend on Age of Onset?

Abstract: ObjectivesTinnitus is the perception of a sound in the absence of any physical source of it. About 5–15% of the population report hearing such a tinnitus and about 1–2% suffer from their tinnitus leading to anxiety, sleep disorders or depression. It is currently not completely understood why some people feel distressed by their tinnitus, while others don't. Several studies indicate that the amount of tinnitus distress is associated with many factors including comorbid anxiety, comorbid depression, personality,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
42
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 21 publications
(27 reference statements)
6
42
1
4
Order By: Relevance
“…An association between tinnitus severity and age has already been suggested earlier [40,41]. It has also been reported that patients with an earlier onset of tinnitus suffer significantly less than patients with an onset later in life [42]. Decline of compensatory brain plasticity in older age has been suggested as an explanation for this age-dependent tinnitus decompensation.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…An association between tinnitus severity and age has already been suggested earlier [40,41]. It has also been reported that patients with an earlier onset of tinnitus suffer significantly less than patients with an onset later in life [42]. Decline of compensatory brain plasticity in older age has been suggested as an explanation for this age-dependent tinnitus decompensation.…”
Section: Discussionmentioning
confidence: 82%
“…Obviously, further factors, which are not reflected by the SCL-90-R, are relevant for tinnitus severity. Among them may be tinnitus loudness, coping behavior, comorbidities such as hearing loss, vertigo, dizziness and hyperacusis, tinnitus duration, age at tinnitus onset and etiology of tinnitus onset, which all have been proposed as factors that have an influence on the quality of life of tinnitus patients [17,[42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…These same brain areas also are responsible for the perception of tinnitus and tinnitus related comorbid distress 7,38,39 i.e., the limbic system responsible for emotions processes the neural impulses it receives from the auditory system 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies demonstrate that the QoL of younger sufferers is far more reduced than the elderly population 5,26 while Pinto et al 43 established no correlation between age and Tinnitus emotional comorbidities. In a large population study, older patients reported greater tinnitus related distress with the explanation that a decline in neuroplasticity with advancing age may be the underlying mechanism 7 . We propose that the younger and more active population will report greater tinnitus related distress as seen in our study because of the recorded significant limitation in daily life functions as a result of tinnitus comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation